Enhance transdermal delivery of flurbiprofen via microemulsions: Effects of different types of surfactants and cosurfactants - Idrees, MA. (Tehran University of Medical Sciences, 2011)
BACKGROUND AND THE PURPOSE OF THE STUDY: Microemulsions are thermodynamically stable, clear dispersions of water, oil, surfactant, and cosurfactant. This study was aimed to develop flurbiprofen microemulsion for enhanced transdermal delivery and investigate the effects of different surfactants and cosurfactants on its delivery and phase behavior. METHOD: Various surfactant-cosurfactant mixtures in ratio of 2:1 (Smix) along with oleic acid (oil) were selected and phase diagrams were constructed. Six microemulsions each containing 5% drug, 5% oil, 56% Smix and 34% water, were prepared and compared for their permeation and phase behaviors to determine the effects of the type of Smix. RESULTS: In vitro transdermal permeation through rabbit skin of all microemulsions was high than saturated aqueous drug solution. Tween 20 and ethanol as Smix produced the highest flux amongst all the Smix, and were used to prepare formulations with different values of oil and Smix. While the type of surfactant did not affect the droplet size, propylene glycol as cosurfactant produced the largest droplets and highest viscosity. Decrease in oil or Smix concentration resulted in decrease of the droplet size and increase in permeation flux while decrease in viscosity also increased the permeation flux of microemulsions. Finally the selected microemulsion formulation comprising 5% flurbiprofen, 5% oleic acid, 46% Tween 20:ethanol (2:1) and 44% water, showed the highest transdermal flux and caused no skin irritation. CONCLUSION: Type of surfactant and cosurfactant affect both the phase behavior and transdermal drug delivery of microemulsion; and results of this study showed that they are promising vehicles for improved transdermal delivery and sustained action of flurbiprofen.